2007
DOI: 10.1016/j.bbrc.2007.04.119
|View full text |Cite
|
Sign up to set email alerts
|

Induction of high STAT1 expression in transgenic mice with LQTS and heart failure

Abstract: Cardiac-specific expression of the N1325S mutation of SCN5A in transgenic mouse hearts (TG-NS) resulted in long QT syndrome (LQTS), ventricular arrhythmias (VT), and heart failure. In this study we carried out oligonucleotide mircoarray analysis to identify genes that are differentially expressed in the TG-NS mouse hearts. We identified 33 genes in five different functional groups that showed differential expression. None of the 33 genes are ion channel genes. STAT1, which encodes a transcription factor involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…The apoptotic response to IFIT2 may contribute to other functions, including translational regulation, inhibition of tumor colonization, and protection against a lethal viral infection [47]. IFIT2 and IFIT3 are the interferon-related genes and are found to be differentially expressed in heart failure mice [48]. In this study, STAT1, IFIT2, and IFIT3 were identified as hub nodes and showed multiple interactions with other genes/proteins.…”
Section: Discussionmentioning
confidence: 69%
“…The apoptotic response to IFIT2 may contribute to other functions, including translational regulation, inhibition of tumor colonization, and protection against a lethal viral infection [47]. IFIT2 and IFIT3 are the interferon-related genes and are found to be differentially expressed in heart failure mice [48]. In this study, STAT1, IFIT2, and IFIT3 were identified as hub nodes and showed multiple interactions with other genes/proteins.…”
Section: Discussionmentioning
confidence: 69%
“…Although the detailed mechanism for apoptosis in TG-NS hearts is not known, activation of caspases 3 and 9, but not caspase-8, suggests that cardiomyocyte apoptosis in these mice is via the mitochondrial apoptotic pathway. An extensive microarray study revealed that expression of STAT1 was markedly increased in TG-NS hearts[23] and such an increase may contribute to increased cardiomyocyte apoptosis[24]. Furthermore, we showed that compared to TG-WTL10 mice, expression of L-type Ca 2+ channel, RYR2, and NCX was increased in TG-NS mice (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Wu et al using the transgenic mice with SCN5A N1325S mutation in the mouse heart (TG‐NS), a mouse model for LQTS, studied global gene expression reprogramming in these mice. Differentially expressed genes between TG‐NS and nontransgenic control mice were determined using mouse oligonucleotide microarrays with 22,690 unique transcripts . Researchers reported a large number of genes with altered expression between these two types of mice.…”
Section: The Use Of Microarrays In the Diagnosis Of Arrhythmiasmentioning
confidence: 99%
“…At P value of 10 −4 , there were 11 differentially expressed genes with fold change values more than 5: nine were activated and two were inhibited (9↑, 2↓). At P value of 10 −3 , there were 33 differentially expressed (31↑, 2↓) genes with ≥ 5‐fold . When the cut off was set to twofold, the number of genes increased to 14 at P ≤ 10 −4 and 65 at P ≤ 10 −3 .…”
Section: The Use Of Microarrays In the Diagnosis Of Arrhythmiasmentioning
confidence: 99%
See 1 more Smart Citation